AQUINAS AND THE OBLIGATIONS OF MERCY - Floyd, Shawn (Journal of religious ethics, 2009)
Contemporary philosophers often construe mercy as a supererogatory notion or a matter of punitive leniency. Yet it is false that no merciful actions are obligatory. Further, it is questionable whether mercy is really about punitive leniency, either exclusively or primarily. As an alternative to these accounts, I consider the view offered by St. Thomas Aquinas. He rejects the claim that we are never obligated to be merciful. Also, his view of mercy is not restricted to legal contexts. For him, mercy's scope is considerably broader, as it concerns a wide range of needs and hardships to which human beings are vulnerable. Such a view, I submit, affords a kind of normative depth lacking in many contemporary accounts. Unlike those views that construe mercy as either a supererogatory or legal concept, Aquinas's account illuminates mercy's obligatory nature and encourages us to make mercy a more salient fixture of our moral lives.